Stress Analysis of CFG Pile Composite Foundation in Consolidating Saturated Mine Tailings Dam - Jinxing Lai; Houquan Liu; Junling Qiu; Haobo Fan; Qian Zhang; Zhinan Hu; Junbao Wang (Advances in Materials Science and Engineering)
Cement fly-ash gravel (CFG) pile is a widely used ground reinforcement technique. This paper aims to address the mechanical characteristics of CFG composite foundation in consolidating saturated mine tailings (MTs) dam. The field static load tests were employed to explore the bearing capacity of the CFG composite foundation, and finite element (FE) models in three dimensions validated through comparison with experimental results were used to discuss the pile-soil stress distribution and pile-soil stress ratio of the CFG composite foundation. The results indicate that the distribution of earth pressure and pile stress is relatively homogeneous and stable over depth and load, while the development of CFG composite foundation bearing capacity is insufficient, in which the developed bearing capacity of CFG piles is less than 50% of its characteristic value. Additionally, compared with the laboratory model test results, the pile-soil stress ratio decreases with the increasing of the load in FEM results proved to better conform to the actual engineering conditions. Furthermore, the deformation modulus and thickness of cushion exert significant influence on pile-soil stress ratio and integral bearing capacity of CFG composite foundation.